Stabilność decyzji administracyjnej w znowelizowanym k.p.a.: [Stability of administrative decisoons in amended code of administrative procedure] (Studia Prawnicze / The Legal Studies, 1981)
The issue of stability of an administrative decision, especially of a decision from which the parties had gained some rights, for many years now has absorbed the thoughts of theorists and practitioners. In contemporary legal science opinions claiming greater stability of decisions were more and more often pronounced in order to guarantee that the citizen can confide to a greater extent in such de- cisions and in organs making them. Notwithstanding the defectiveness of a final decision, factors favoring stability were pointed out, such as the lapse of time, impossibility to recall legal results of some decisions, and often, lack of fault of the party empowered by a defective decision when it relied on competence of the organ.Studies on efficacy of the code of administrative procedure during 17 years of its existence, undertaken by the commissions of the Diet thanks to the iniciative of the member of the Diet, prof. S. Zawadzki, proved among other things that setting decisions aside occured too often, somentimes without due reason, and that provisions of the code in its I960 — version did not constitute sufficient barrier to such a phenomenon. The law of 1980 which amended the code to a significant extent, solved this problem in a double way. On the one hand new provisions pay greater attention to preparatory and evidenciary proceedings and to fuller realization of the principle of two-instances of proceedings (even in case of a decision of a minister made in the first instance can one claim new hearing as to the merits which thus constitutes a quasi-appeal). On the other hand, these provisions find their counterpart in provisions considerably limiting the possibi- lity of setting a final defective decision aside when it awards certain rights to a party.The most important factor which stabilizes a defective decision is the lapse of time. Apart from some exceptions this is 5 or 10 years period counting from the day of serving of a final decision to the parties or from its public pronounce- ment. This principle concerns some specific situations in which proceedings may be reopened (a trial de novo) and those in which decisions may be declaredinvalid by organs of administrative control or by the Chief Administrative Court. New provisions bar setting final decisions aside also in such situations when the same decision as to the merits would have to be made in result of new proceedings in the instances or when a decision previously made had provoked legal consequences not to be recalled any more.The party damaged by setting aside or by declaring a decision invalid, as well as the party damaged due to impossibility of setting aside a defective decision because of the reasons mentioned above, can claim compensation unless the decision was made because of the fault of such party. Responsibility of the Treasury will thus constitute further factor stimulating proper decision-making. Also, introduction of the system of control of legality of final administrative de- cisions by the court - as a principle of the system - gives better guaranty that the rights of administrative organs to change, repeal or declare invalidity of final decisions will not be abused.